TINJAUAN YURIDIS PENIPUAN TRANSAKSI PEMBELIAN HANPHONE MELALUI INSTAGRAM DAN WHATSAPP - Hapsari, Nia Puspita (Lex Jurnalica, 2025)
The lack of public social media awareness via Instagram and WhatsApp they are still tempted by discounts or promotions for buying and selling cellphones. In the Criminal KHU Law Number 82 of 2012 Electronic Systems, Transactions and Criminal Crimes Against Cyber Crime perpetrators. The research analyzes legal protection against fraudulent purchases when buying and selling cell phones via Instagram and WhatsApp. Researchers used the method from field research and normative juridical, data obtained by interviewing victims/consumers, library materials, statutory regulations, and normative empirical juridical. The expected results of the methods for reporting buying and selling fraud via social media and victims regulated by Law No.31 of 2014 on consumer witness/victims protection. The conclusion is that legal officials, especially the police, will investigate more deeply the perpetrators of the crime of buying and selling cell phone fraud, and to what extent the perpetrators of the fraud were caught and imprisoned.